Supervisory management : the management of effective supervision - Miranda, Gregorio S. (Mandaluyong City, Philippines : National Book Store, 1999)
This book gives the reader an insight into the ramifications that surround this important managerial function.
CHAPTER 1. The task of managing -- 2. The Supervisor - The Firing Line -- 3. Functions and Responsibilities of supervisors -- 4. Leadership Qualities -- 5. Selection and Placement -- 6. Directing and Counseling -- 7. the Foreman in the industrial Organization -- 8. The New Supervisor -- 9. Span of supervision -- 10. Supervising Employees -- 11. developing Employees -- 12. Supervisory Training -- 13. Maintaining Discipline -- 14. Handling Employee Grievance -- 15. Motivation and Morale -- 16. Communication -- 17. performance evaluation -- 18. Setting work performance standards -- 19. Supervisory Development.
Includes bibliographical references.
Keywords: SUPERVISORS